PENGARUH MODEL BRALANCING BERBANTUAN MEDIA FLIPBOOK ETH-NOMATEMATIK TERHADAP LITERASI NUMERASI SISWA KELAS IV SD N GUGUS I KECAMATAN BUSUNGBIU (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the Bralancing (Brain Balance Learning) learning model assisted by ethnomathematic Flipbook media on the numeracy literacy of fourth-grade students of Elementary School Cluster I, Busungbiu District. This study uses a quantitative approach with a quasi-experimental type and a nonequivalent control group design. The study population was all fourth-grade students of Elementary School Cluster I, Busungbiu District, with a sampling technique using purposive sampling. Data were collected through numeracy literacy tests, then analyzed using descriptive and inferential analysis (normality test, homogeneity test, and hypothesis test). The results showed that there was a significant effect of the use of the Bralancing model assisted by ethnomathematic Flipbook on students' numeracy literacy. This was indicated by the increase in learning outcomes in the experimental class which was higher than the control class. The Bralancing model was able to optimize the balance of right and left brain work and increase student engagement, while the ethnomathematic Flipbook media provided a contextual and interesting learning experience. Thus, the Bralancing model assisted by ethnomathematic Flipbook media was effectively used as an innovative alternative in improving elementary school students' numeracy literacy. Keywords: Bralancing, Flipbook, Ethnomathematics, Numeracy Literacy, Elementary School.